Formation of Crystalline Telluridomercurates from Ionic Liquids near Room Temperature. Issue 1 (10th November 2016) - Donsbach, Carsten; Dehnen, Stefanie
Abstract : The ternary telluridomercurate Na2 [HgTe2 ] (1 ) was formed by fusion of Na2 Te and HgTe at 600 °C and further treated in the ionic liquid (C4 C1 Im)[BF4 ] (C4 C1 Im = 1‐butyl‐3‐methylimidazolium) at moderately elevated temperatures (60 °C), leading to replacement of the Na + cations with (C4 C1 Im) + and re‐arrangement of the inorganic substructure. As a result, we obtained the telluridomercurate (C4 C1 Im)2 [HgTe2 ] (2 ) and the tellurido/ditelluridomercurate (C4 C1 Im)2 [Hg2 Te4 ] (3 ) besides polytellurides and HgTe as by‐products. The heavy atom compositions of the compounds were confirmed by micro X‐ray fluorescence spectroscopy (μ‐XFS), and their structures were determined by single‐crystal diffraction. The cation‐exchanged salts were further investigated by UV/Vis spectroscopy, indicating narrow band‐gap optical transitions at 2.80 eV (2 ) and 1.63 eV (3 ), in agreement with their visible yellow or reddish‐black color, respectively. Abstract :